Epidemi Penyakit Antraknosa pada Tanaman Jeruk Nipis [Citrus aurantifolia (christm.) Swingle] di Desa Kertalangu, Kecamatan Denpasar Timur - NI WAYAN SUNITI; I KETUT SUADA; I MADE SUDARMA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
ABSTRACT The Epidemic of Anthracnose Disease in the Lemon [Citrus aurantifolia (Christm.) Swingle] at Kertelangu Village, East Denpasar District Anthracnose disease on lemon was a newly discovered disease in Kertalangu Village, East Denpasar. Status of the disease unknown,. and lemon plants grown less well maintained and neglected, almost all plants showing symptoms of disease. Planting conditions like this it's possible anthracnose disease that can destroy rapidly growing cultivation of lemon. The research was conducted from April to June 2015 in the village of Kertalangu, district East Denpasar, Bali. The results showed that the leaf spot disease found on lemon was anthracnose that caused by Colletotrichum gloeosporioides. Disease incidence of anthracnose was 26.16 – 35.00%, and disease severity was 17.38 – 24.10%, that is mean relatively mild disease. The infection of rate was 0.00128 – 0.0162 per leaf per day, its mean development of the disease was slowly. Keywords: Anthracnose, Colletotrichum gloeosporioides, inhibiting ability, prevalence, endophytic and exophytic.